Aspects of Selecting Appropriate Conveyor Belt Strength - Dariusz Woźniak; Monika Hardygóra (Energies, 2021)
Breaks in the so-called “continuous” (unspliced) belt sections, and not in the spliced areas, are infrequent but do happen in practice. This article presents some aspects, which may account for such breaks in conveyor belts. It indicates the so-called “sensitive points” in design, especially in the transition section of the conveyor belt and in identifying the actual strength of the belt. The presented results include the influence of the width of a belt specimen on the identified belt tensile strength. An increase in the specimen width entails a decrease in the belt strength. The research involved develops a universal theoretical model of the belt on a transition section of a troughed conveyor in which, in the case of steel-cord belts, the belt is composed of cords and layers of rubber, and in the case of a textile belt, of narrow strips. The article also describes geometrical forces in the transition section of the belt and an illustrative analysis of loads acting on the belt. Attention was also devoted to the influence of the belt type on the non-uniform character of loads in the transition section of the conveyor. A replacement of a conveyor belt with a belt having different elastic properties may increase the non-uniformity of belt loads in the transition section of the conveyor, even by 100%.